The evaluation of physicochemical and anti-microbial properties of honey based hydrogel - Abdul Jalil, Mohd Azri; Kasmuri, Abdul Razak; Ab. Hadi, Hazrina (Malaysian Pharmaceutical Society, 2017)
NTRODUCTION: Hydrogel possess a three-dimensional cross linked networks of hydrophilic polymers. Honey contain anti-microbial properties due to its peroxide and non-peroxide components.OBJECTIVES: To develop and characterize honey based hydrogel formulation and to evaluate its anti-microbial properties. METHODS: The hydrogel were developed by combining polyvinyl alcohol (PVA) and polyethylene glycol (PEG). 1% protein-free agar was added to the combination as well as honey according to their respective formulations. Then, the characterization tests consist of gel fraction, swelling ratio and water vapour transmission (WVTR) were conducted. For the antimicrobial evaluation, microbial limit test and agar diffusion test were conducted against Staphylococcus aureus and Pseudomonas aeruginosa. RESULTS: For the gel fraction test, the control formulation was significantly (p<0.05) highest among the others; indicates that the PVA in this formulation was almost completely cross-linked. For the swelling ratio test, formulation 2 that contain 20% (w/v) honey was significantly (p<0.05) higher than the control and agar groups; indicates a higher water uptake occurred. The WVTR of formulation 2 was within the recommended range which is in between 80–105gm -2day -1. Formulation 5 with 40% (w/v) honey has shown anti-microbial effect towards Staphylococcus aureus. For microbial limit tests, all formulations showed the absence of bacteria in their respective surfaces.CONCLUSIONS: Formulation 2 demonstrated significantly better physicochemical properties but displaying no anti-microbial properties. However, formulation 5 showed an acceptable physicochemical properties but able to display a good anti-microbial properties. Therefore, formulation 5 will be selected for further studies. Keywords: hydrogel, honey, anti-microbial